Evaluation of groundwater quality in Palu-Sigi Biromaru post-liquefaction, Central Sulawesi, Indonesia - Afandi, Moh Fahri; Wilopo, Wahyu; Pranantya, Pulung Arya (Journal of Degraded and Mining Lands Management, 2025)
The liquefaction phenomenon on September 28, 2018, in Palu, particularly in Petobo and Jono Oge, caused severe damage and disrupted the shallow aquifer system. This study compared groundwater quality in the non-liquefaction area and the liquefaction area before and after the 2018 earthquake in South Palu and Sigi Biromaru, Central Sulawesi, Indonesia. The data were collected through field and laboratory analyses in 2025 and secondary data in 2018, before the earthquake, from previous researchers. The parameters of groundwater, including physicochemical properties, major ions, stable isotopes (?¹?O-?²H), and E. coli. The results show that non-liquefaction areas remained stable, characterized by Ca-HCO? facies and isotopes close to LMWL, which reflect local meteoric recharge. In contrast, post-liquefaction areas exhibited significant increases in Na?, Cl?, SO?²?, and NO?? along with high content of E. coli bacteria, resulting from a combination of geological processes and anthropogenic activities. Liquefaction also causes land degradation due to the loss of the soil's humus layer, as well as soil pollution from the remains of building materials that collapse during the liquefaction process. These findings confirm that liquefaction accelerates ion mobilization, increases the biological vulnerability of aquifers, and reduces soil quality.